История создания и развития отдела горной аэрогазодинамики - Абрамова, Ф.А.; Шматовский, Л.Д. (Геотехническая механика, 2012)
Викладено історію і напрямки розвитку відділу гірничої аерогазотемодинаміки - найстарішого у інституті (відділ існує задовго до офіційного затвердження інституту, і був підпорядкований ФІМ УРСР), який декілька модернізувався: від нього неодноразово відокремлювалися інші підрозділи. Це – відділи член-кореспондента АН УРСР Ф.О. Абрамова, професорів Р.Б. Тяна, Ю.А. Цейтліна, Г.А. Шевельова, В.В. Виноградова, кандидатів техн. наук В.Я. Потьомкіна та М.М. Хачапурідзе. Зараз цей напрям продовжується у відділі, головою якого є академік НАН України А.Ф. Булат. Відділи багато років займалися проблемами викидів вугілля, породи і газу, аерогазотермодинаміки, протиаварійного захисту шахт. History and directions of development of department of mountain aerogazodynamyky is laid out - the more oldest in an institute (a department exists long before official claim of institute, and was inferior to FIM of USSR) which a few was modernized: other subsections became separated from from him repeatedly. This are departments of the corresponding member AS of USSR F.A.Abramova, professors R.B. Tjana, J.A.Tseitlina, G.A. Sheveljova, V.V. Vinogradova, candidates of 99 теcn. sciences V.J. Potjomkina and N.М. Khachapuridzae. Now this direction proceeds in a department the chairman of which there is the academician of NAS of Ukraine А.F. Bulat. During a lot of years, these departments studied problems of coal, rock and gas outbursts, air-and-gas dynamics,and emergency protection in mines.